SEMANTIC ANALYSIS OF 2019 POLITICAL JARGON IN PRESIDENT AND VICE PRESIDENT ELECTION IN INDONESIA - Dede irawan (Universitas Majalengka, 2018)
This research aimed to know the semantic meaning of the 2019 political jargon presidential and vice presidential election. Nowadays both of candidate use the jargon to convey the political program especially to make an opinion in society. Based on the data analysis, it was found out political jargon a both of candidates use connotative and social meaning to influence the public, language rhetoric is very inherent in “Adil makmur” jargon is more explore propaganda that uses poverty sentiment with comparing between rich and poor.Whereas in the political jargon that uses Mr. Jokowi dodo and K.H Mahruf Amin “ Bersih, Merakyat, Kerja Nyata